The Role of Moral Considerations in Blockchain Technology and Its Impact on Tax Compliance: A Literature Review - I Gusti Putu Eka Rustiana Dewi (Pusat Riset dan Inovasi Nasional, 2025)
This study of the literature examines the interaction between blockchain technology and moral considerations, with a particular emphasis on its impact on tax compliance. Blockchain's incorporation into tax systems creates both new ethical options and concerns as it continues to transform data security, transparency, and traceability. This paper explores the ethical dimensions of tax compliance within digital environments through a qualitative literature review. The study reviews previous research on the relationship between taxpayers' moral ideals, ethical decision-making, and perceptions of tax justice and the intrinsic properties of blockchain, such as immutability and decentralization. According to the findings, moral factors—such as social norms, individual ethical frameworks, and trust in institutions—have a significant impact on how taxpayers behave in blockchain-based settings. The review also emphasizes how blockchain can improve voluntary tax compliance by increasing transparency, but it can also have drawbacks if moral considerations are ignored. This study provides a conceptual framework for researchers and policymakers who want to create tax systems that are both ethically sound and technologically sophisticated by combining insights from interdisciplinary studies.